EQUAÇÃO DE VOLUME DE APLICABILIDADE EXTENSIVA A DIVERSAS CLASSES DE IDADE PARA PINUS TAEDA L. NA REGIÃO MEIO OESTE DO ESTADO DE SANTA CATARINA - TÉO, Saulo Jorge; MACHADO, Sebastião do Amaral; FIGUEIREDO FILHO, Afonso; TOMÉ, Margarida (Brazilian Journal of Biometrics, 2018)
The aim of this study was to develop volume equations for Pinus taeda L., inside and outside bark, with extensive applicability to several age classes. Data came from 631 trees of Pinus taeda, with ages ranging from 4 to 31 years, of different stands distributed in several counties of the Middle West region of Santa Catarina State, Brazil. The volume models Näslund Modified, Péllico Netto, Schumacher and Hall, Spurr and Tomé were tested, which were fit in their simple formulation and with their coefficients linear function of the stand age. After selecting the best performing model, it was submitted to validation and comparison between its simple formulation and the formulation with the coefficients linear function of the age. The inclusion of coefficients linear function of the age in the Schumacher and Hall model contributed to improve the accuracy and precision of inside and outside bark volume estimates, of Pinus taeda.